Morphological Study of Human Kidney A Post Mortem Study (Bangladesh Journal of Anatomy, 2014)
Context: Retroperitoneal location of kidney implies much difficulties in management of renal diseases, specially for surgeons. Appropriate knowledge on three dimensional morphological status of kidney may be helpful for successful surgery of this region. So this study was performed to evaluate the age related changes in length, breadth and thickness of kidney collected from Bangladesh. Materials and methods: A cross sectional analytical type of study was conducted at the department of Anatomy, Mymensingh Medical College, Mymensingh, Bangladesh. A total of 70 (seventy) fresh human of right & left kidneys of both sexes were collected from the morgue of Mymensingh Medical College. The selected cases were between 5 to 60 years of age. The samples were divided into 3 different age groups (A: 05-15 years, B: 16-35 years, C: 36- 60 years) to observe the variations in length, breadth and thickness of kidney. Results: Statistically significant differences were found in the values of length, breadth and thickness among these groups except the difference of values regarding breadth and thickness between group C & A which were not significant (P > 0.05). Conclusion: There were changes in the values of length, breadth and thickness of kidneys DOI: http://dx.doi.org/10.3329/bja.v11i1.20500 Bangladesh Journal of Anatomy, January 2013, Vol. 11 No. 1 pp 3-6